2013
DOI: 10.1002/jcb.24404
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of GPC3 inhibits the proliferation of Huh7 hepatocellular carcinoma cells through down‐regulation of YAP

Abstract: Glypican-3 (GPC3), a membrane-associated heparan sulfate proteoglycan, is frequently upregulated in hepatocellular carcinoma (HCC). Yes-associated protein (YAP) is also found over-expressed in HCC and has been identified as a key effector molecule in Hippo pathway, which could control the organ size in animals through the regulation of cell proliferation and apoptosis and plays an important role in the development of malignant tumors. Studies have reported that GPC3 and YAP might collaborate to regulate the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
3
32
0
1
Order By: Relevance
“…Furthermore, we showed that both endogenous and exogenous GPC3 expression were correlated with metastasis and invasion. First, we found endogenous GPC3 expression was associate with HCC metastasis in HCC tissues and cells, which was consistent with the report from Miao et al that the knockdown of GPC3 resulted in the inhibition of cell migration and invasion in Huh7 cells (16). The migration and invasion capacities of HCC cell lines were also increased by exogenous GPC3 treatment, suggesting that in addition to endogenous GPC3, soluble/exogenous GPC3 may also function to promote HCC metastasis in patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, we showed that both endogenous and exogenous GPC3 expression were correlated with metastasis and invasion. First, we found endogenous GPC3 expression was associate with HCC metastasis in HCC tissues and cells, which was consistent with the report from Miao et al that the knockdown of GPC3 resulted in the inhibition of cell migration and invasion in Huh7 cells (16). The migration and invasion capacities of HCC cell lines were also increased by exogenous GPC3 treatment, suggesting that in addition to endogenous GPC3, soluble/exogenous GPC3 may also function to promote HCC metastasis in patients.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have reported that GPC3 can stimulate the migration, and invasion (16,17) of HCC cell lines. Here, we focused on the clinical importance of GPC3 in HCC, and noted that there was a positive association between GPC3 expression and HCC metastasis progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al [19] and Murthy et al [40] found that GPC3 re-expression in ovarian cancer cell lines resulted in inhibition of the efficiency of colony formation. Some studies have shown that GPC3 plays an important role in cell growth and differentiation [41, 42], such as in the case of hepatocellular carcinoma [43]. The data obtained in the present study suggest that GPC3 inhibits cell proliferation in clear cell renal cell carcinoma.…”
Section: Discussionsupporting
confidence: 72%
“…Участие некоторых гепатопротекторов и иммуномодуляторов в регуляции апоптоза гепатоцитов, индуцированного противотуберкулезными препаратами основного ряда Доказано, что апоптоз гепатоцитов играет важную роль в патогенезе многих заболеваний: вирусных гепати-тов [1,2], алкогольных поражений печени [3] и других па-тологических состояний [4,5]. В настоящее время отме-чено увеличение числа лекарственных поражений печени [6].…”
unclassified